Recovery of reactive MgO from reject brine via the addition of NaOH - Dong, Haoliang (2018)
Reject brine, generated as a waste at the end of the desalination process, presents a useful 18 source for the extraction of valuable resources. This study investigated the recovery of 19 reactive MgO from reject brine obtained from a local desalination plant. This was enabled via 20 the reaction of Mg2+ present within reject brine with an alkali source (NaOH), which led to 21 the precipitation of Mg(OH)2, along with a small amount of CaCO3. The determination of the 22 optimum NaOH/Mg2+ ratio led to the production of the highest amount of yield. The 23 synthesized Mg(OH)2 was further calcined under a range of temperatures (500-700 °C) and 24 durations (2-12 hours) to produce reactive MgO. A detailed characterization of MgO 25 obtained under these conditions was presented in terms of its reactivity, specific surface area 26 (SSA), composition and microstructure. While an increase in the calcination temperature and 27 duration decreased the reactivity and SSA of MgO, samples calcined at 500 °C for 2 hours 28 revealed the highest reactivity, which was reflected by their SSA of 51.4 m2/g.